2014
DOI: 10.2217/nnm.14.113
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Long-Term Biodistribution Studies of a Pamam Dendrimer G5–Gd-BnDOTA Conjugate for Lymphatic Imaging

Abstract: Aims To demonstrate the use of gadolinium (Gd)-labeled dendrimers as lymphatic imaging agents and establish the long-term biodistribution (90-day) of this type of agent in mice. Materials & methods A G5-Gd-BnDOTA dendrimer was prepared and injected into mice and monkeys for MR lymphangiography, and long-term biodistribution of the conjugate was studied. Results Administration of G5–Gd-BnDOTA in mice demonstrated a rapid uptake in the deep lymphatic system while injection in monkeys showed enhanced internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The observation of the SAP and TSAP isomers using HPLC was reported in Gd-pSCN BnDOTA and Eu-pNO2-BnDOTA 32 , however this is the first report that studied the interconversion of isomers across the lanthanide series using HPLC. The use of different types of C18 columns and mobile phase conditions (with and without TFA) did not change the elution profile of the isomers.…”
Section: Resultsmentioning
confidence: 90%
“…The observation of the SAP and TSAP isomers using HPLC was reported in Gd-pSCN BnDOTA and Eu-pNO2-BnDOTA 32 , however this is the first report that studied the interconversion of isomers across the lanthanide series using HPLC. The use of different types of C18 columns and mobile phase conditions (with and without TFA) did not change the elution profile of the isomers.…”
Section: Resultsmentioning
confidence: 90%
“…Dual contrast agents can be used to improve clinical diagnosis, since single modal signals can give false positive diagnosis of lesions due to background signals in neighbouring tissues. However, bioaccumulation of these dendrimer-conjugates in organs remains an issue, limiting their clinical applications [49].…”
Section: Imaging Agentsmentioning
confidence: 99%
“…4,5 Generation 5 (G5) PAMAM dendrimers are the most promising scaffolds due to their spherical and flexible structure, well-defined molecular weight, fine size (approximately 5 nm), and proper amount of surface groups (128 branches) for the conjugation of therapeutics or diagnostic agents. 6 Recently, researchers found that low generation (G ≤ 4) dendrimers have certain bioactivities and functions.…”
Section: ■ Introductionmentioning
confidence: 99%